Move Fast and Break Things? Barriers to GovTech Procurement in the United Kingdom - Davies, Nathan; McBride, Keegan; Kleinaltenkamp, Moritz (Conference on Digital Government Research, 2025)
Governments depend on procurement to help them achieve their digital transformation goals. Historically, public sector technology contracts have overwhelmingly flowed to large technology firms. However, governments have begun to explore opening up the procurement process to GovTech startups to drive innovation. Yet, this policy goal has proved challenging to implement. This paper explores why this is the case by presenting the case study of GovTech startup procurement in the United Kingdom. By focusing on the role of temporal dynamics in shaping procurement processes and drawing on 32 primary interviews with stakeholders across the UK GovTech ecosystem and supplementary archival data, this study identifies how the financial, staffing, and strategic processes within public sector bureaucracies enact an erratic and unpredictable procurement rhythm. It further demonstrates the challenges startups face when encountering this rhythm, struggling to predict or synchronise with it. Startups who are successful face new challenges from managing multiple rhythms. While conventional discourse often frames this procurement challenge as a mismatch between the "slow" public sector and "fast" startups, this paper instead reveals the complex and contradictory rhythms that frustrate GovTech procurement.